Implementasi Konsep Pendidikan Agama Islam dalam Mengatasi Bullying: Studi Kasus di Pesantren Zainul Hasan Genggong - Azkalakum Zakiyullah; Ainur Rofiq Sofa (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to apply the concept of Islamic Religious Education (PAI) in addressing bullying, both verbal and non-verbal, at Zainul Hasan Genggong Islamic Boarding School. This research also examines the forms of implementing the PAI concept as a preventive measure against bullying, as well as the factors that support and hinder its implementation. The approach used in this study is qualitative with a case study design. Data were collected through observation, interviews, and documentation, involving various informants such as the boarding school leaders, counselors, and students. The results show that the PAI concept is implemented through the formation of noble character based on the teachings of the Qur'an and the Hadith of Prophet Muhammad SAW. The implementation of the PAI concept at Zainul Hasan Genggong Islamic Boarding School includes character development for students, improving social cohesion, fostering manners, providing educational punishments, rewards, and role modeling. Supporting factors include full support from the boarding school administration and involvement of student guardians, while challenges include resistance from some students toward behavior changes and limited resources. The study concludes that the implementation of the PAI concept has successfully created a safer and more conducive boarding school environment, reducing bullying practices among students.